The Prescription Characteristics, Efficacy and Safety of Spironolactone in Real-World Patients With Acute Heart Failure Syndrome: A Prospective Nationwide Cohort Study - Na, Soo Jin; Youn, Jong-Chan; Lee, Hye Sun; Jeon, Soyoung; Lee, Hae-Young; Cho, Hyun-Jai; Choi, Jin-Oh; Jeon, Eun-Seok; Lee, Sang Eun; Kim, Min-Seok; Kim, Jae-Joong; Hwang, Kyung-Kuk; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Randomized clinical trials of spironolactone showed significant mortality reduction in patients with heart failure with reduced ejection fraction. However, its role in acute heart failure syndrome (AHFS) is largely unknown. Aim: To investigate the prescription characteristics, efficacy and safety of spironolactone in real-world patients with AHFS. Methods: 5,136 AHFS patients who survived to hospital discharge using a nationwide prospective registry in Korea were analyzed. The primary efficacy outcome was 3-year all-cause mortality. Results: Spironolactone was prescribed in 2,402 (46.8%) at discharge: < 25 mg in 890 patients (37.1%), ≥ 25 mg and < 50 mg in 1,154 patients (48.0%), and ≥ 50 mg in 358 patients (14.9%). Patients treated with spironolactone had a lower proportion of chronic renal failure and renal replacement therapy during hospitalization and had lower serum creatinine level than those who did not. In overall patients, 3-year mortality was not different in both groups (35.9% vs. 34.5%, P=0.279). The incidence of renal injury and hyperkalemia was 2.2% and 4.3%, respectively, at the first follow-up visit. The treatment effect of spironolactone on mortality was different across subpopulations according to LVEF. The use of spironolactone was associated with a significant reduction in 3-year morality in patients with LVEF ≤ 26% (33.8% vs. 44.3%, P<0.001; adjusted HR 0.79, 95% CI 0.64-0.97, P=0.023), but not in patients with LVEF > 26%. Conclusions: Although spironolactone was frequently used at lower doses in real-world practice, use of spironolactone significantly reduced 3-year mortality in patients with severely reduced LVEF with acceptable safety profile. However, our findings remain prone to various biases and further prospective randomized controlled studies are needed to confirm these findings.